Characterization of Salubrious Germinated Rice (Oryza sativa L.) Laddus for Physico – Nutritional Attributes and Shelf Life Stability: Standardisation and evaluation of rice laddu - W, Jessie Suneetha; Amma, Akhila; B, Anila Kumari; J, Hemantha Kumar; M, Sreenivasulu (Journal of Cereal Research, 2025)
Cereals form significant part of global diet and most developing nations rely heavily on rice as a staple food. Rice (Oryza sativa L) is one of the important cereals with easy digestibility and therapeutic properties. The laddu prepared using raw rice as control, germinated siddi and BPT 5204 rice-based health mixes were analyzed for the physico-chemical parameters and shelf stability.The colour difference of siddi laddu to control for L*, a*, b*, ∆E, C* and h* were less than 10.0%. There was statistically significant difference at p ≤ 0.05 between the samples for total sugars, total starch, amylose and amylopectin. The total sugars, reducing sugars, non-reducing sugars, total starch, amylopectin and amylose contents were more or less similar for both experimental and control laddus.The control and experimental laddu showed water activity content of 0.77±0.06 and 0.68± 0.09%, moisture content of 7.84±0.19 and 7.35±0.17%, ash of 1.74±0.00 and 1.84±0.01%, protein 15.37±0.42 and 16.81±0.12%, fat 7.41±0.12 and 8.16±0.18%, crude fiber 1.49±0.00 and 1.42±0.02%, carbohydrates 66.31±0.23 and 62.22±0.13% and energy 388.1±0.09 and 385.70±0.08 Kcal/100g respectively with statistically significant difference at p ≤ 0.05 for the samples except for ash and crude fibre.Better results were for laddus with germinated siddi rice than germinated BPT 5204 rice like longer shelf life. The microbial quality assessment of laddus revealed increased total bacterial count that were within safer limits and zero mould growth during storage period of 15 days at ambient temperature and 30 days under refrigeration in air tight containers.